Crossroads of Belief: Religious Conversion and the Political Dimensions Among Indigenous Peoples in Indonesia - Suryani, Ade Jaya (JURNAL PENELITIAN, 2024)
This research examines the political dimensions of religious conversion among Indigenous Peoples in Indonesia, focusing on the experiences of the Baduy in Banten, the Akur Sunda Wiwitan in West Java, and the Suku Anak Dalam in Jambi. It aims to understand how political structures—particularly state policies and identity politics—drive religious conversion, often under the pretext of social inclusion. While conventional studies on conversion emphasize psychological or sociocultural factors, this research situates conversion within the broader framework of political hegemony and state control over officially recognized religions. Employing a qualitative methodology, this research draws on fieldwork, in-depth interviews, and documentary analysis, integrating anthropological, sociological, and political science approaches. The findings indicate that religious conversion among Indigenous groups is often not spiritually motivated but rather a strategic response to institutional discrimination, legal exclusion, and the pursuit of citizenship rights. This highlights the crucial role of state power in shaping religious identities and marginalizing traditional belief systems. By foregrounding the non-Western realities of political coercion and exclusion, this research contributes to the decolonization of conversion studies. It calls for policy reforms that uphold religious freedom and protect Indigenous religious identities within a pluralistic and democratic framework.